Epistemological Reconstruction of Islamic Education: Developing a Transformative Pedagogical Model to Foster Creativity - Mardatillah, Fuadi; Gumilang, Randi Muhammad; Wahyudi, M. Agus; Rawanita, Mesi; Muhammad, Muhammad (SCAD Independent, 2025)
Islamic education in Indonesia is confronted with a critical challenge in cultivating creativity, critical thinking, and intellectual independence among students. Entrenched in rigid and traditionalist pedagogical models, the system often fails to accommodate the dynamic and creative dimensions of human potential, resulting in educational stagnation and diminished societal relevance. This study addresses this issue by exploring the epistemological reconstruction of Islamic education, aiming to develop a transformative educational framework rooted in creativity, rationality, and moral responsibility. The study integrates insights from classical Islamic scholarship and modern educational theory by employing a qualitative methodology based on a comprehensive literature review and analytical-reflective analysis. The proposed model emphasizes the need to deconstruct the dichotomy between religious and scientific knowledge, promote epistemological universality, and adopt pluralistic, student-centered learning approaches. The findings reveal that revitalizing Islamic education through such a framework can foster pious, creative, autonomous, and socially engaged learners. Ultimately, this article argues for an educational paradigm that does not merely preserve religious tradition but actively prepares individuals to become ethical contributors to a just, inclusive, and civilized society. The study also highlights the importance of further research to test this model in real institutional contexts.